Comparison of one-stage anteroposterior and posterior-alone hemivertebrae resection combined with posterior correction for hemivertebrae deformity - Wang, Lei (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: The surgical technique of hemivertebrae excision varies from anteroposterior procedures to posterior-alone resections according to the experience and preference of surgeons. Both the approaches are reliable and give relatively good results. This study aims to evaluate and compare the clinical and radiological results of these two approaches for hemivertebrae resection. MATERIALS AND METHODS: Sixty patients were retrospectively enrolled between 2006 and 2009. The subjects included 32 women and 28 men, with a mean age of 12.9 years (range: 5–24 years). Thirty patients who underwent one-stage anteroposterior hemivertebrae resection (the AP group) were followed for 38.5 months, and the other 30 patients who underwent posterior resection (the P group) were followed for 20.6 months. Clinical and radiological assessments were performed preoperatively, 1 week postoperatively, and at the final follow-up. The operation time, blood loss, degree of correction of the main curve/segmental curve/kyphosis, the average hospital stay, and complications were reviewed and compared between the two groups. RESULTS: The mean operation time, blood loss, and hospital stay of the AP group and the P group were 451 min vs 248.5 min, 1290 ml vs 910 ml, and 21.93 days vs 18.97 days, respectively (P<.05). The average correction rate of the main curve/segmental curve/kyphosis of the AP group and the P group was 68.5% vs 66.2%, 71.5% vs 69.6%, and 57.4% vs 56.1%, respectively (P>.05). Overall complication rate was 6.7% in the AP group vs 10% in the P group (P>.05). CONCLUSION: Posterior hemivertebrael resection is a promising approach for congenital scoliosis in terms of relative safety, degree of correction achieved, reduced operative time and blood loss.